Peran Kompetensi Kepribadian Guru dalam Membentuk Lingkungan Belajar Siswa: Studi Literatur - Anisa Siti Nurhaliza; Mochammad Fikri Haikal; Mursidin Mursidin; Ayi Muammar (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the role of teachers’ personality competence in shaping students’ learning environments through a literature review approach. Personality competence reflects teachers’ stable, mature, and authoritative character, enabling them to serve as role models for students and influencing the creation of a conducive learning environment both psychologically and socially. The method used is a literature review by analyzing various sources such as books, academic journals, and relevant official documents. The results show that teachers with positive personality traits are able to build harmonious relationships, create a comfortable classroom atmosphere, and enhance students’ learning motivation. Therefore, teachers’ personality competence is an important factor in supporting the quality of the learning environment and the success of the learning process. In addition, findings from various studies indicate that personality competence not only affects classroom interactions but also contributes to the development of students’ attitudes, discipline, and emotional stability. Teachers who demonstrate consistency, empathy, and integrity tend to foster a sense of trust and respect among students, which further strengthens classroom engagement. Moreover, a positive teacher personality helps reduce learning barriers such as anxiety, lack of confidence, and lack of participation in classroom activities. In the context of modern education, where student-centered learning is increasingly emphasized, teachers’ personality competence becomes even more essential in facilitating active learning and meaningful student involvement. Thus, strengthening teachers’ personality competence through training, reflective practice, and continuous professional development is crucial to improving overall educational quality and achieving optimal learning outcomes.